Cost-effectiveness analysis of atezolizumab plus bevacizumab versus sorafenib in first line treatment for Chinese subpopulation with unresectable hepatocellular carcinoma - Tseng, Chien-Yu; Tsai, Yi-Wen; Shiu, Ming-Neng (Frontiers in Oncology, 2023)
Objective We aimed to evaluate the cost-effectiveness of atezolizumab plus bevacizumab (atezo-bev) versus sorafenib treatment in Taiwan. Methods Using sorafenib as the comparator, we developed a partitioned survival model to evaluate the costs and quality-adjusted life year (QALY) of the atezo-bev treatment. The time horizon of the study was 15 years, and the annual discount rate was 3%. We analyzed the incremental cost-effectiveness ratio (ICER) and incremental net monetary benefit (INMB) from the treatment effects (determined from the progression-free and overall survival outcomes of the IMbrave150 study), direct medical costs (collected and estimated from the National Health Insurance Research Database, Taiwan), and utility parameters (referred to the NICE technology appraisal guidance), as well as the deterministic sensitivity and probabilistic sensitivity. Results Compared with sorafenib, the incremental effectiveness of atezo-bev treatment was 1.7 QALY, with an incremental cost of USD 127,607. The ICER was USD 75,192 per QALY, which was less than the predefined willingness to pay in Taiwan. Conclusion The combined treatment of atezo-bev is cost-effective when compared with sorafenib, which is currently the first-line treatment option for unresectable HCC in Taiwan.